From “Grupos de Trabajo” to “Colectivos”: The Evolution of Armed Pro-Government Groups in the Chávez Era - Velasco, Alejandro (Espacio Abierto, 2022)
The term “colectivo” has arguably become one of the most widely deployed, and fraught, words in the Chávez era. Nominally used to refer to a particular subset of pro-government supporters – namely, para-state groups who employ armed violence to enforce the government’s hold on power – conceptually and empirically “colectivos” remain significantly understudied a phenomenon, by some described as “paramilitaries,” by others as “vigilantes,” even at times speculated to control as much as ten percent of Venezuela. This paper seeks to cut through the conceptual and empirical confusion surrounding the term. Instead it offers a comprehensive assessment of the evolution of armed pro-government groups with very diverse origins, organizational structures, ideological postures, relationships with the state, and repertories of contention, but that nevertheless came to be encapsulated under the umbrella term “colectivo” and in doing so, eliding important nuances that may provide a fuller picture of how chavismo transitioned from a participatory democratic project, to a top-down socialist project, to an authoritarian state, to a nation on the verge of collapse. It asks: how did the rise into prominence and notoriety of groups once seen as fringe in chavismo’s early years, even undesirable by Chavez himself, take place, and what does the Maduro government’s growing reliance on such groups suggest about the state (both as condition and as governance system) of chavismo today?